Cell‐free tumour DNA testing for early detection of cancer – a potential future tool. (8th April 2019) - Barbany, G.; Arthur, C.; Liedén, A.; Nordenskjöld, M.; Rosenquist, R.; Tesi, B.; Wallander, K.; Tham, E.
Abstract: In recent years, detection of cell‐free tumour DNA (ctDNA) or liquid biopsy has emerged as an attractive noninvasive methodology to detect cancer‐specific genetic aberrations in plasma, and numerous studies have reported on the feasibility of ctDNA in advanced cancer. In particular, ctDNA assays can capture a more 'global' portrait of tumour heterogeneity, monitor therapy response, and lead to early detection of resistance mutations. More recently, ctDNA analysis has also been proposed as a promising future tool for detection of early cancer and/or cancer screening. As the average proportion of mutated DNA in plasma is very low (0.4% even in advanced cancer), exceedingly sensitive techniques need to be developed. In addition, as tumours are genetically heterogeneous, any screening test needs to assay multiple genetic targets in order to increase the chances of detection. Further research on the genetic progression from normal to cancer cells and their release of ctDNA is imperative in order to avoid overtreating benign/indolent lesions, causing more harm than good by early diagnosis. More knowledge on the sources and elimination of cell‐free DNA will enable better interpretation in older individuals and those with comorbidities. In addition, as white blood cells are the major source of cell‐free DNA in plasma, it is important to distinguish acquired mutations in leukocytes (benign clonal haematopoiesis) from an upcoming haematological malignancy or other cancer. In conclusion, although many studies report encouraging results, further technical development and larger studies are warranted before applying ctDNA analysis for early cancer detection in the clinic. Abstract :